Efficiency optimisation of gas turbine based cogeneration cycle - Yilmaz, T.; Bayraktar, S.; Tasci, F. (MANEY PUBLISHING, 2008)
This paper presents an optimisation of a cogeneration system based on alternative performance criteria. The system includes a gas turbine which is operated in a Brayton cycle and a heat recovery steam generator (HRSG). In the analysis, total produced exergy, energy utilisation factor (EUF), artificial thermal efficiency and exergy efficiency have been defined as function of the design parameters of the gas turbine and the HRSG. The optimum values of the design parameters of the cogeneration cycle were determined for different criteria. In this context, the effects of design parameters on the exergetic performance are investigated and the results are discussed. The obtained results may guide towards a more realistic criterion for actual cogeneration plants.
Keywords: performance criteria; performance optimisation; cogeneration cycle; HRSG; EXERGY OPTIMIZATION; SYSTEM; Energy & Fuels